Ultrahigh-moisture-absorption anti-static polyester fiber and preparation method thereof

By preparing modified benzisothiazolinone, modified cyclophosphazene and modified zinc-aluminum oxide, combined with polyethylene terephthalate and pore-generating agent, it forms modified polyester fibers with high hygroscopicity, antibacteriality, antistatic and flame retardant, solving the problems of poor hygroscopicity, strong electrostaticity, insufficient antibacteriality and flame retardancy in existing polyester textiles.

CN119593207APending Publication Date: 2025-03-11JIANGSU SUNFENG SPECIAL MATERIAL TECH CO LTD +1

Patent Information

Application Number
CN202411566402.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-11

Smart Images

  • Figure CN119593207A_ABST
    Figure CN119593207A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fibers, and discloses an ultrahigh-moisture-absorption anti-static polyester fiber and a preparation method thereof. The preparation method comprises the following steps: carrying out nucleophilic substitution reaction on 1, 2-benzisothiazolin-3-one and methacryloyl chloride to obtain modified benzisothiazolinone; the preparation method comprises the following steps: carrying out nucleophilic substitution reaction on phosphonitrilic chloride trimer and allylamine, and then carrying out nucleophilic substitution reaction on the phosphonitrilic chloride trimer and melamine again to obtain modified cyclophosphazene; the preparation method comprises the following steps: mixing gamma-methacryloxypropyltrimethoxysilane with aluminum zinc oxide for reaction, and mixing the obtained modified aluminum zinc oxide with modified benzisothiazolinone and modified cyclophosphazene for copolymerization in the presence of an initiator to obtain a flame-retardant antibacterial additive; mixing the flame-retardant antibacterial additive, calcium carbonate and polyethylene glycol terephthalate, performing melt spinning, and performing acid treatment to obtain modified polyester fibers; dipping the modified polyester fiber in a finishing liquid containing modified chitosan to obtain the ultrahigh-moisture-absorption anti-static polyester fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fibers, and in particular to an ultra-high moisture absorption antistatic polyester fiber and a preparation method thereof. Background Art

[0002] Polyester fabric is a widely used clothing fabric. Due to its poor hygroscopicity and low regain, it is easy to generate static electricity during processing and wearing, which makes it uncomfortable to wear and easy to feel stuffy. After long-term use, the fabric is easy to breed a large number of bacteria or microorganisms, affecting its practicality and safety. At the same time, polyester fiber is a flammable fiber, which is easy to decompose and burn and spread rapidly, posing a great hidden danger to fire safety. Therefore, improving the hydrophilic hygroscopicity, antibacterial and flame retardancy of polyester textiles can improve the wearing comfort and practical safety of polyester fabrics, reduce the incidence of fire and the loss of life and property, and is of great significance in expanding the application of polyester textiles. The schemes for improving the comprehensive performance of polyester in the prior art are mostly to add auxiliaries in the dyeing and shaping section of polyester to improve the hygroscopicity, antistatic and other properties of polyester, but the obtained modified polyester has poor washing resistance and its performance is seriously degraded after washing.

[0003] Prior art, such as Chinese patent application CN110616472A, discloses a method for preparing antibacterial fabrics with antistatic properties, which adds a modifier to polyester polyester to make the obtained polyester polyester contain a large number of hydrophilic groups, and introduces antibacterial agent quaternary ammonium salt in a chemically bonded manner, thereby improving the hygroscopicity, antistatic and antibacterial properties of the polyester polyester. However, the flame retardancy of the polyester produced needs to be improved, and the process of preparing polyester polyester is complicated and has strict process requirements, which is not conducive to large-scale process production. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide an ultra-high hygroscopic antistatic polyester fiber and a preparation method thereof. The polyester fiber has high hygroscopicity, excellent antibacterial property, antistatic property and excellent flame retardancy.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing ultra-high moisture absorption antistatic polyester fiber comprises the following steps:

[0007] Step (1), preparation of modified benzisothiazolinone and modified cyclophosphazene

[0008] Wherein, the preparation of modified benzisothiazolinone comprises the following steps:

[0009] Mix 1,2-benzisothiazolin-3-one, dichloromethane and pyridine, add methacryloyl chloride dropwise, react after the addition is complete, wash, dehydrate, filter, take the filtrate, and remove the solvent dichloromethane by rotary evaporation to obtain modified benzisothiazolinone;

[0010] Wherein, the preparation of modified cyclophosphazene comprises the following steps:

[0011] The hexachlorocyclotriphosphazene is mixed with tetrahydrofuran, and a mixed solution of allylamine / triethylamine is added dropwise. After the addition is completed, the mixture is reacted. After the reaction is completed, the mixture is filtered and the filtrate is taken. After the reaction is completed, melamine is added to the filtrate and the reaction is continued. After the reaction is completed, the tetrahydrofuran and triethylamine are removed by rotary evaporation, and the mixture is washed and dried to obtain a modified cyclophosphazene.

[0012] Step (2), mixing zinc aluminum oxide and ethanol by ultrasonication, adding γ-methacryloxypropyltrimethoxysilane after ultrasonication and mixing evenly, then adding a regulator to adjust the pH value, and performing a first reaction. After the reaction is completed, filtering, washing, and drying to obtain modified zinc aluminum oxide;

[0013] The modified benzisothiazolinone, the modified cyclophosphazene, the modified zinc oxide aluminum, ammonium persulfate and water are mixed, reacted for the second time, filtered, washed and dried after the reaction is completed, and a flame retardant antibacterial additive is obtained;

[0014] Step (3), mixing the flame retardant and antibacterial additive, calcium carbonate and polyethylene terephthalate, melt spinning, cooling, drawing and chopping to obtain a crude modified polyester fiber product, mixing the crude modified polyester fiber product with an aqueous solution of hydrochloric acid, reacting, filtering, washing and drying after the reaction is completed to obtain the modified polyester fiber;

[0015] Step (4), mixing chitosan, acetic acid, aqueous hydrogen peroxide solution and water, reacting, adding a regulator to adjust the pH value after the reaction is completed, filtering, washing and drying to obtain modified chitosan;

[0016] The modified chitosan, acetic acid, malonic acid, sodium acetate and water are mixed to obtain a finishing liquid; the modified polyester fiber is mixed with the finishing liquid, immersed, and after the immersion is completed, washed and dried to obtain an ultra-high moisture absorption antistatic polyester fiber.

[0017] Preferably, in the step (1), when preparing the modified benzisothiazolinone: the mass ratio of 1,2-benzisothiazolin-3-one, dichloromethane, pyridine and methacryloyl chloride is 5-5.5:33-36:4-4.4:5.5-6; the dropping conditions are: dropping at room temperature for 20-30 minutes; and the reaction conditions are: reacting at room temperature for 1-2 hours.

[0018] Preferably, the dehydration operation comprises: taking the washed organic phase, adding 20% ​​of the mass of the organic phase anhydrous sodium sulfate, and standing and dehydrating for 8-12 hours.

[0019] Preferably, in the step (1), when preparing the modified cyclophosphazene, the mass ratio of hexachlorocyclotriphosphazene, tetrahydrofuran, allylamine / triethylamine mixed solution, and melamine is 6.5-7:45-50:6.5-8:6-8; the dropwise addition conditions are: dropwise addition for 20-30 min at a speed of 1500-2000 r / min and room temperature in a nitrogen atmosphere; the reaction conditions are: reaction for 4-8 h at a temperature of 0-5° C. in a nitrogen atmosphere; and the continued reaction conditions are: continued reaction for 16-18 h at a temperature of 80-85° C. in a nitrogen atmosphere.

[0020] Preferably, the allylamine / triethylamine mixed solution is prepared by mixing allylamine, triethylamine and tetrahydrofuran in a mass ratio of 1:7-8:0.5-0.8.

[0021] Preferably, in step (2), the mass ratio of zinc oxide aluminum, ethanol and γ-methacryloxypropyltrimethoxysilane is 8-10:280-320:3-5; and the first reaction conditions are: the first reaction is carried out at a temperature of 60-70° C. for 10-16 hours.

[0022] Preferably, the regulator comprises a 0.1 mol / L hydrochloric acid aqueous solution, and the adjusted pH value is 5-5.5.

[0023] Preferably, in step (2), the mass ratio of modified benzisothiazolinone, modified cyclophosphazene, modified zinc aluminum oxide, ammonium persulfate and water is 25-30:55-60:100:5-6:1500-1800; the second reaction conditions are: in a nitrogen atmosphere, at a temperature of 80-85°C for 5-6h.

[0024] Preferably, in the step (3), the mass ratio of the flame retardant and antibacterial additive, calcium carbonate and polyethylene terephthalate is 3-5:5:90-92; the melt spinning conditions are: melt extrusion through a twin-screw melt spinning machine under the condition that the temperature of each zone of the extruder is 270-275°C, and spinning is carried out at a spinning speed of 1800-3200m / min.

[0025] Preferably, in step (3), the mass ratio of the modified polyester fiber crude product to the hydrochloric acid aqueous solution is 1:30; the reaction conditions are: reaction at 75-80°C for 0.5-1h; the fineness of the modified polyester fiber is 15-30D, the average length is 38mm, and the fiber cross-section is a cross shape.

[0026] Furthermore, the hydrochloric acid aqueous solution is a 1 mol / L hydrochloric acid aqueous solution.

[0027] Preferably, in step (4), the mass ratio of chitosan, acetic acid, aqueous hydrogen peroxide solution and water is 30-50:20-25:30-40:1000, the aqueous hydrogen peroxide solution is 30 wt % aqueous hydrogen peroxide solution; and the reaction conditions are: react at room temperature for 2-3 hours.

[0028] Preferably, the regulator comprises sodium hydroxide, and the pH value after adjustment is 8-9.

[0029] Preferably, in step (4), the mass ratio of modified chitosan, acetic acid, malonic acid, sodium acetate and water is 25-30:10-20:3:4:1000; the mass ratio of modified polyester fiber to finishing liquid is 1:20; and the dipping operation includes: dipping at room temperature for 1-1.5 hours, two dippings and two rollings, and the rolling rate is 80%.

[0030] Preferably, an ultra-high hygroscopic antistatic polyester fiber is prepared by the method for preparing the ultra-high hygroscopic antistatic polyester fiber as described above.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] Isothiazolinone compounds have an isothiazolinone ring, have strong killing properties against fungi, bacteria, and algae, and have excellent antibacterial properties and low toxicity. In the present invention, 1,2-benzisothiazolin-3-one with antibacterial properties undergoes a nucleophilic substitution reaction with methacryloyl chloride, so that the obtained modified benzisothiazolinone has a double bond, which can be used as a reaction monomer to copolymerize with other monomers containing double bonds and a carrier, so that the antibacterial component is not easy to migrate.

[0033] Phosphazene compounds have a large amount of phosphorus, nitrogen and phosphorus-nitrogen six-membered ring structure, so they have excellent flame retardant ability. In the present invention, hexachlorocyclotriphosphazene and allylamine undergo nucleophilic substitution reaction, so that allylamine is grafted on hexachlorocyclotriphosphazene, and after the reaction, the remaining chlorine on the hexachlorocyclotriphosphazene and melamine undergo nucleophilic substitution reaction again to obtain a modified cyclophosphazene with a triazine structure and a double bond. Among them, the triazine structure and the phosphazene structure in the modified cyclophosphazene together constitute an intumescent flame retardant, which has a synergistic flame retardant effect, and the double bond group provides an active group for the modified cyclophosphazene, so that it can be used as a reactive monomer, and combined with other monomers containing double bonds and a carrier through a polymerization reaction between double bonds, so that it is not easy to migrate.

[0034] Zinc oxide aluminum is a composite material composed of zinc oxide and aluminum oxide, and has excellent electrical conductivity. After surface treatment with γ-methacryloxypropyltrimethoxysilane, the modified zinc oxide aluminum obtained has a carbon-carbon double bond, and then mixed with modified benzisothiazolinone and modified cyclophosphazene for copolymerization, the dispersibility of zinc oxide aluminum in the matrix and the stability of modified benzisothiazolinone and modified cyclophosphazene are improved, the modified benzisothiazolinone and modified cyclophosphazene are not easy to migrate, and the flame retardant and antibacterial additive obtained has flame retardant, antibacterial and antistatic effects.

[0035] The present invention obtains modified polyester fiber by adding a porogen and a flame retardant and antibacterial additive to polyethylene terephthalate, and performing melt spinning and acid treatment. The amino groups on the surface of the flame retardant and antibacterial additive react with the terminal carboxyl groups of the polyethylene terephthalate molecular chain in a molten state to graft the flame retardant and antibacterial additive onto the chain segments of polyethylene terephthalate, thereby making it have better dispersibility and compatibility in polyethylene terephthalate, and improving the antibacterial and flame retardant properties and mechanical properties of polyester; the porogen is dissolved during the acid treatment process, so that the obtained modified polyester fiber has a microporous structure, thereby improving the hygroscopicity of the modified polyester fiber, and at the same time, since the modified polyester fiber has polar amide bonds, it can form hydrogen bonds with water molecules, so the hydrophilicity of the fiber is increased to a certain extent, thereby further improving the hygroscopicity of the modified polyester fiber.

[0036] The present invention impregnates the modified polyester fiber with low molecular weight modified chitosan. Since the modified chitosan molecule contains a large amount of amino and hydroxyl groups and has antibacterial effect, and the microporous structure on the modified polyester fiber increases the surface area of ​​the fiber, more modified chitosan can be loaded, thereby further improving the hygroscopicity of the modified polyester fiber. Therefore, the ultra-high hygroscopic antistatic polyester fiber obtained has ultra-high hygroscopicity, antistatic property, antibacterial property and flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a process flow chart for preparing ultra-high moisture absorption antistatic polyester fiber in the present invention;

[0038] Figure 2 It is a bar graph of the antibacterial rates of the ultra-high moisture absorption and antistatic polyester fibers prepared in Examples 1-5 and Comparative Examples 1-3 of the present invention in the antibacterial performance test;

[0039] Figure 3 It is a bar graph of the moisture absorption rate of the ultra-high moisture absorption antistatic polyester fibers prepared in Examples 1-5 and Comparative Examples 1-3 of the present invention in the moisture absorption performance test;

[0040] Figure 4It is a bar graph of the limiting oxygen index of fabrics 1-8 prepared from the ultra-high moisture absorption and antistatic polyester fibers prepared in Examples 1-5 and Comparative Examples 1-3 in the flame retardant performance test of the present invention. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] This embodiment discloses a method for preparing ultra-high moisture absorption antistatic polyester fiber, comprising the following steps:

[0044] Step (1), preparation of modified benzisothiazolinone and modified cyclophosphazene

[0045] Wherein, the preparation of modified benzisothiazolinone comprises the following steps:

[0046] 1,2-Benzisothiazoline-3-one, dichloromethane and pyridine were mixed, methacryloyl chloride was added dropwise at room temperature for 30 minutes, and the reaction was carried out at room temperature for 1 hour after the addition was completed. After the reaction was completed, a reaction product was obtained, and water 5 times the mass of the reaction product was added to wash three times. The organic phase was taken, and anhydrous sodium sulfate 20% of the mass of the organic phase was added. The organic phase was allowed to stand for dehydration for 12 hours, filtered, and the filtrate was taken. The solvent dichloromethane was removed by rotary evaporation at 35°C to obtain modified benzisothiazolinone;

[0047] Among them, the mass ratio of 1,2-benzisothiazolin-3-one, dichloromethane, pyridine and methacryloyl chloride is 5.5:36:4.4:6;

[0048] Wherein, the preparation of modified cyclophosphazene comprises the following steps:

[0049] Mix hexachlorocyclotriphosphazene with tetrahydrofuran, add a mixed solution of allylamine / triethylamine dropwise at room temperature in a nitrogen atmosphere at a rotation speed of 2000 r / min for 30 min, react for 4 h in a nitrogen atmosphere at 5°C after the addition is complete, filter and take the filtrate after the reaction is complete, add melamine to the filtrate, continue to react for 16 h in a nitrogen atmosphere at 85°C, and after the reaction is complete, remove tetrahydrofuran and triethylamine by rotary evaporation at 60°C to obtain a reaction product, add water twice the mass of the reaction product for washing, and dry at 50°C for 12 h to obtain a modified cyclophosphazene;

[0050] The mass ratio of hexachlorocyclotriphosphazene, tetrahydrofuran, allylamine / triethylamine mixed solution and melamine is 7:50:8:8; the allylamine / triethylamine mixed solution is prepared by mixing allylamine, triethylamine and tetrahydrofuran in a mass ratio of 1:7:0.5;

[0051] Step (2), mixing zinc aluminum oxide and ethanol with ultrasonic treatment, adding γ-methacryloxypropyltrimethoxysilane after ultrasonic treatment and mixing evenly, then adding 0.1 mol / L hydrochloric acid aqueous solution to adjust the pH value to 5.5, reacting for the first time at 60° C. for 16 h, filtering after the reaction, taking the filter cake, adding ethanol and water in an amount of 8 times the mass of the filter cake to wash in sequence, and drying at 50° C. for 12 h to obtain modified zinc aluminum oxide; wherein the mass ratio of zinc aluminum oxide, ethanol, and γ-methacryloxypropyltrimethoxysilane is 10:320:5;

[0052] Modified benzisothiazolinone, modified cyclophosphazene, modified zinc aluminum oxide, ammonium persulfate and water were mixed in a mass ratio of 30:60:100:6:1800, and reacted for a second time at 85°C in a nitrogen atmosphere for 5 hours. After the reaction, the mixture was filtered, the filter cake was taken, ethanol in an amount of 8 times the mass of the filter cake was added for washing, and the mixture was dried at 50°C for 12 hours to obtain a flame retardant antibacterial additive.

[0053] Step (3), mixing a flame retardant and antibacterial additive, calcium carbonate, and polyethylene terephthalate in a mass ratio of 5:5:90, melt-extruded through a twin-screw melt spinning machine under the condition that the temperature of each zone of the extruder is 275° C., spinning at a spinning speed of 3200 m / min, cooling, drawing, and chopping to obtain a modified polyester fiber crude product, mixing the modified polyester fiber crude product with a 1 mol / L hydrochloric acid aqueous solution in a mass ratio of 1:30, reacting at a temperature of 75° C. for 1 h, filtering after the reaction, taking a filter cake, adding water 5 times the mass of the filter cake for washing, and drying at a temperature of 95° C. for 3 h to obtain a modified polyester fiber with a fineness of 15D and an average length of 38 mm;

[0054] Wherein, during the melt spinning process, the cross section of the spinneret hole is in a cross shape, and the fiber cross section of the modified polyester fiber is in a cross shape;

[0055] Step (4), chitosan, acetic acid, 30wt% hydrogen peroxide aqueous solution, and water are mixed in a mass ratio of 50:25:40:1000, reacted at room temperature for 3 hours, and after the reaction is completed, sodium hydroxide is added to adjust the pH value to 8, filtered, and the filter cake is taken, washed with water 5 times the mass of the filter cake, and dried at 60°C for 10 hours to obtain modified chitosan;

[0056] Modified chitosan, acetic acid, malonic acid, sodium acetate and water are mixed in a mass ratio of 30:20:3:4:1000 to obtain a finishing liquid; the modified polyester fiber is mixed with the finishing liquid in a mass ratio of 1:20, immersed in the mixture for 1.5 hours at room temperature, and rolled twice with a rolling rate of 80%. After the immersion, water 5 times the mass of the modified polyester fiber is added for washing, and the fiber is dried at 40°C for 12 hours to obtain an ultra-high moisture absorption and antistatic polyester fiber.

[0057] Example 2

[0058] This embodiment discloses a method for preparing ultra-high moisture absorption antistatic polyester fiber, comprising the following steps:

[0059] Step (1), preparation of modified benzisothiazolinone and modified cyclophosphazene

[0060] Wherein, the preparation of modified benzisothiazolinone comprises the following steps:

[0061] 1,2-Benzisothiazoline-3-one, dichloromethane and pyridine were mixed, methacryloyl chloride was added dropwise at room temperature for 20 minutes, and the reaction was carried out at room temperature for 2 hours after the addition was completed. After the reaction was completed, a reaction product was obtained, and water twice the mass of the reaction product was added to wash three times. The organic phase was taken, and anhydrous sodium sulfate of 20% of the mass of the organic phase was added, and the mixture was allowed to stand for dehydration for 8 hours, filtered, and the filtrate was taken, and the solvent dichloromethane was removed by rotary evaporation at 30°C to obtain modified benzisothiazolinone;

[0062] Among them, the mass ratio of 1,2-benzisothiazolin-3-one, dichloromethane, pyridine, and methacryloyl chloride is 5:33:4:5.5;

[0063] Wherein, the preparation of modified cyclophosphazene comprises the following steps:

[0064] Hexachlorocyclotriphosphazene was mixed with tetrahydrofuran, and an allylamine / triethylamine mixed solution was added dropwise at room temperature in a nitrogen atmosphere at a rotation speed of 1500 r / min for 20 min. After the addition was completed, the mixture was reacted in a nitrogen atmosphere at a temperature of 0°C for 8 h. After the reaction was completed, the mixture was filtered and the filtrate was taken. Melamine was added to the filtrate, and the mixture was reacted for 18 h in a nitrogen atmosphere at a temperature of 80°C. After the reaction was completed, tetrahydrofuran and triethylamine were removed by rotary evaporation at a temperature of 50°C to obtain a reaction product, and water 5 times the mass of the reaction product was added for washing, and the mixture was dried at a temperature of 60°C for 8 h to obtain a modified cyclophosphazene.

[0065] The mass ratio of hexachlorocyclotriphosphazene, tetrahydrofuran, allylamine / triethylamine mixed solution and melamine is 6.5:45:6.5:6; the allylamine / triethylamine mixed solution is prepared by mixing allylamine, triethylamine and tetrahydrofuran in a mass ratio of 1:8:0.8;

[0066] Step (2), mixing zinc aluminum oxide and ethanol with ultrasonic treatment, adding γ-methacryloxypropyltrimethoxysilane after ultrasonic treatment and mixing evenly, then adding 0.1 mol / L hydrochloric acid aqueous solution to adjust the pH value to 5, reacting for the first time at 70° C. for 10 h, filtering after the reaction, taking the filter cake, adding ethanol and water with a mass of 5 times the mass of the filter cake to wash in sequence, and drying at 60° C. for 8 h to obtain modified zinc aluminum oxide; wherein the mass ratio of zinc aluminum oxide, ethanol, and γ-methacryloxypropyltrimethoxysilane is 8:280:3;

[0067] The modified benzisothiazolinone, the modified cyclophosphazene, the modified zinc aluminum oxide, the ammonium persulfate and the water were mixed in a mass ratio of 25:55:100:5:1500, and the mixture was reacted for a second time at 80°C in a nitrogen atmosphere for 6 hours. After the reaction, the mixture was filtered, the filter cake was taken, ethanol 5 times the mass of the filter cake was added for washing, and the mixture was dried at 60°C for 8 hours to obtain a flame retardant antibacterial additive.

[0068] Step (3), mixing a flame retardant and antibacterial additive, calcium carbonate, and polyethylene terephthalate in a mass ratio of 4.5:5:90.5, melt-extruded through a twin-screw melt spinning machine under the condition that the temperature of each zone of the extruder is 270° C., spinning at a spinning speed of 1800 m / min, cooling, drawing, and chopping to obtain a modified polyester fiber crude product, mixing the modified polyester fiber crude product with a 1 mol / L hydrochloric acid aqueous solution in a mass ratio of 1:30, reacting at a temperature of 80° C. for 0.5 h, filtering after the reaction, taking a filter cake, adding water 8 times the mass of the filter cake for washing, and drying at a temperature of 90° C. for 4 h to obtain a modified polyester fiber with a fineness of 20D and an average length of 38 mm;

[0069] Wherein, during the melt spinning process, the cross section of the spinneret hole is in a cross shape, and the fiber cross section of the modified polyester fiber is in a cross shape;

[0070] Step (4), chitosan, acetic acid, 30wt% hydrogen peroxide aqueous solution, and water are mixed in a mass ratio of 30:20:30:1000, reacted at room temperature for 2h, and after the reaction is completed, sodium hydroxide is added to adjust the pH value to 9, filtered, the filter cake is taken, and water of 8 times the mass of the filter cake is added for washing, and dried at 50°C for 18h to obtain modified chitosan;

[0071] Modified chitosan, acetic acid, malonic acid, sodium acetate and water are mixed in a mass ratio of 29:18:3:4:1000 to obtain a finishing liquid; the modified polyester fiber is mixed with the finishing liquid in a mass ratio of 1:20, immersed in room temperature for 1 hour, twice immersed and twice rolled, and the rolling rate is 80%. After the immersion, 8 times the mass of the modified polyester fiber is added for washing, and dried at 30°C for 24 hours to obtain an ultra-high moisture absorption and antistatic polyester fiber.

[0072] Example 3

[0073] This embodiment discloses a method for preparing ultra-high moisture absorption antistatic polyester fiber, comprising the following steps:

[0074] Step (1), preparation of modified benzisothiazolinone and modified cyclophosphazene

[0075] Wherein, the preparation of modified benzisothiazolinone comprises the following steps:

[0076] 1,2-Benzisothiazoline-3-one, dichloromethane and pyridine were mixed, methacryloyl chloride was added dropwise at room temperature for 25 minutes, and the reaction was carried out at room temperature for 1.5 hours. After the reaction was completed, a reaction product was obtained, and water 3 times the mass of the reaction product was added to wash three times. The organic phase was taken, and anhydrous sodium sulfate 20% of the mass of the organic phase was added. The organic phase was allowed to stand for dehydration for 10 hours, filtered, and the filtrate was taken. The solvent dichloromethane was removed by rotary evaporation at 32°C to obtain modified benzisothiazolinone;

[0077] Among them, the mass ratio of 1,2-benzisothiazolin-3-one, dichloromethane, pyridine and methacryloyl chloride is 5.2:35:4.2:5.8;

[0078] Wherein, the preparation of modified cyclophosphazene comprises the following steps:

[0079] Hexachlorocyclotriphosphazene is mixed with tetrahydrofuran, and an allylamine / triethylamine mixed solution is added dropwise at room temperature in a nitrogen atmosphere at a rotation speed of 1800 r / min for 25 min. After the addition is completed, the mixture is reacted in a nitrogen atmosphere at a temperature of 2° C. for 6 h. After the reaction is completed, the mixture is filtered and the filtrate is taken. Melamine is added to the filtrate, and the mixture is reacted for 17 h in a nitrogen atmosphere at a temperature of 82° C. After the reaction is completed, the tetrahydrofuran and triethylamine are removed by rotary evaporation at a temperature of 55° C. to obtain a reaction product, and water 3 times the mass of the reaction product is added for washing, and the mixture is dried at a temperature of 55° C. for 10 h to obtain a modified cyclophosphazene.

[0080] The mass ratio of hexachlorocyclotriphosphazene, tetrahydrofuran, allylamine / triethylamine mixed solution and melamine is 6.8:48:7:7; the allylamine / triethylamine mixed solution is prepared by mixing allylamine, triethylamine and tetrahydrofuran in a mass ratio of 1:7:0.6;

[0081] Step (2), mixing zinc aluminum oxide and ethanol with ultrasound, after ultrasound, adding γ-methacryloxypropyltrimethoxysilane and mixing evenly, then adding 0.1 mol / L hydrochloric acid aqueous solution to adjust the pH value to 5.2, reacting for the first time at 65° C. for 14 hours, filtering after the reaction, taking the filter cake, adding ethanol and water with a mass of 6 times the mass of the filter cake to wash in sequence, and drying at 55° C. for 10 hours to obtain modified zinc aluminum oxide; wherein the mass ratio of zinc aluminum oxide, ethanol, and γ-methacryloxypropyltrimethoxysilane is 9:300:4;

[0082] Modified benzisothiazolinone, modified cyclophosphazene, modified zinc aluminum oxide, ammonium persulfate and water were mixed in a mass ratio of 28:58:100:5:1600, and reacted for a second time at 83°C in a nitrogen atmosphere for 5.5 hours. After the reaction was completed, the mixture was filtered, the filter cake was taken, ethanol 6 times the mass of the filter cake was added for washing, and the mixture was dried at 55°C for 10 hours to obtain a flame retardant antibacterial additive.

[0083] Step (3), mixing a flame retardant and antibacterial additive, calcium carbonate, and polyethylene terephthalate in a mass ratio of 4:5:91, melt-extruded through a twin-screw melt spinning machine under the condition that the temperature of each zone of the extruder is 273° C., spinning at a spinning speed of 2500 m / min, cooling, drawing, and chopping to obtain a modified polyester fiber crude product, mixing the modified polyester fiber crude product with a 1 mol / L hydrochloric acid aqueous solution in a mass ratio of 1:30, reacting at a temperature of 78° C. for 0.8 h, filtering after the reaction, taking a filter cake, adding water 6 times the mass of the filter cake for washing, and drying at a temperature of 93° C. for 3.5 h to obtain a modified polyester fiber with a fineness of 24D and an average length of 38 mm;

[0084] Wherein, during the melt spinning process, the cross section of the spinneret hole is in a cross shape, and the fiber cross section of the modified polyester fiber is in a cross shape;

[0085] Step (4), chitosan, acetic acid, 30wt% hydrogen peroxide aqueous solution, and water are mixed in a mass ratio of 40:22:35:1000, and reacted at room temperature for 2.5 hours. After the reaction is completed, sodium hydroxide is added to adjust the pH value to 8.5, and the filter cake is filtered, and washed with water 6 times the mass of the filter cake, and dried at 55°C for 16 hours to obtain modified chitosan;

[0086] Modified chitosan, acetic acid, malonic acid, sodium acetate and water are mixed in a mass ratio of 28:15:3:4:1000 to obtain a finishing liquid; the modified polyester fiber is mixed with the finishing liquid in a mass ratio of 1:20, immersed in room temperature for 1 hour, twice immersed and twice rolled, and the rolling rate is 80%. After the immersion, 6 times the mass of the modified polyester fiber is added for washing, and dried at 35°C for 18 hours to obtain an ultra-high moisture absorption and antistatic polyester fiber.

[0087] Example 4

[0088] This embodiment discloses a method for preparing ultra-high moisture absorption antistatic polyester fiber, comprising the following steps:

[0089] Step (1), preparation of modified benzisothiazolinone and modified cyclophosphazene

[0090] Wherein, the preparation of modified benzisothiazolinone comprises the following steps:

[0091] Mix 1,2-benzisothiazolin-3-one, dichloromethane and pyridine, add methacryloyl chloride dropwise at room temperature for 25 minutes, react at room temperature for 2 hours after the addition is complete, and obtain a reaction product after the reaction is complete. Add water 3 times the mass of the reaction product and wash it three times. Take the organic phase, add anhydrous sodium sulfate 20% of the mass of the organic phase, stand and dehydrate for 10 hours, filter, take the filtrate, and remove the solvent dichloromethane by rotary evaporation at 30°C to obtain modified benzisothiazolinone;

[0092] Among them, the mass ratio of 1,2-benzisothiazolin-3-one, dichloromethane, pyridine and methacryloyl chloride is 5.4:35:4.4:5.8;

[0093] Wherein, the preparation of modified cyclophosphazene comprises the following steps:

[0094] Hexachlorocyclotriphosphazene was mixed with tetrahydrofuran, and an allylamine / triethylamine mixed solution was added dropwise at room temperature in a nitrogen atmosphere at a rotation speed of 1600 r / min for 25 min. After the addition was completed, the mixture was reacted in a nitrogen atmosphere at a temperature of 4° C. for 5 h. After the reaction was completed, the mixture was filtered and the filtrate was taken. Melamine was added to the filtrate, and the mixture was reacted for 17 h in a nitrogen atmosphere at a temperature of 80° C. After the reaction was completed, tetrahydrofuran and triethylamine were removed by rotary evaporation at a temperature of 55° C. to obtain a reaction product, which was washed with water 5 times the mass of the reaction product, and dried at a temperature of 60° C. for 8 h to obtain a modified cyclophosphazene.

[0095] The mass ratio of hexachlorocyclotriphosphazene, tetrahydrofuran, allylamine / triethylamine mixed solution and melamine is 6.5:46:6.5:6.5; the allylamine / triethylamine mixed solution is prepared by mixing allylamine, triethylamine and tetrahydrofuran in a mass ratio of 1:7:0.5;

[0096] Step (2), mixing zinc aluminum oxide and ethanol with ultrasonic treatment, adding γ-methacryloxypropyltrimethoxysilane after ultrasonic treatment and mixing evenly, then adding 0.1 mol / L hydrochloric acid aqueous solution to adjust the pH value to 5.5, reacting for the first time at 60° C. for 16 h, filtering after the reaction, taking the filter cake, adding ethanol and water in an amount of 8 times the mass of the filter cake to wash in sequence, and drying at 55° C. for 10 h to obtain modified zinc aluminum oxide; wherein the mass ratio of zinc aluminum oxide, ethanol, and γ-methacryloxypropyltrimethoxysilane is 10:310:4;

[0097] The modified benzisothiazolinone, the modified cyclophosphazene, the modified zinc aluminum oxide, the ammonium persulfate and the water were mixed in a mass ratio of 25:56:100:5:1500, and the mixture was reacted for a second time at 80°C in a nitrogen atmosphere for 5.5 hours. After the reaction was completed, the mixture was filtered, the filter cake was taken, ethanol in an amount of 8 times the mass of the filter cake was added for washing, and the mixture was dried at 55°C for 10 hours to obtain a flame retardant antibacterial additive.

[0098] Step (3), mixing a flame retardant and antibacterial additive, calcium carbonate, and polyethylene terephthalate in a mass ratio of 3.5:5:91.5, melt-extruded through a twin-screw melt spinning machine under the condition that the temperature of each zone of the extruder is 275° C., spinning at a spinning speed of 2800 m / min, cooling, drawing, and chopping to obtain a modified polyester fiber crude product, mixing the modified polyester fiber crude product with a 1 mol / L hydrochloric acid aqueous solution in a mass ratio of 1:30, reacting at a temperature of 80° C. for 0.5 h, filtering after the reaction, taking a filter cake, adding water 8 times the mass of the filter cake for washing, and drying at a temperature of 95° C. for 3 h to obtain a modified polyester fiber with a fineness of 28D and an average length of 38 mm;

[0099] Wherein, during the melt spinning process, the cross section of the spinneret hole is in a cross shape, and the fiber cross section of the modified polyester fiber is in a cross shape;

[0100] Step (4), chitosan, acetic acid, 30 wt% hydrogen peroxide aqueous solution, and water are mixed in a mass ratio of 35:21:32:1000, reacted at room temperature for 2 hours, and after the reaction is completed, sodium hydroxide is added to adjust the pH value to 9, filtered, and the filter cake is taken, washed with water 8 times the mass of the filter cake, and dried at 50° C. for 18 hours to obtain modified chitosan;

[0101] Modified chitosan, acetic acid, malonic acid, sodium acetate and water are mixed in a mass ratio of 26:12:3:4:1000 to obtain a finishing liquid; the modified polyester fiber is mixed with the finishing liquid in a mass ratio of 1:20, immersed in room temperature for 1 hour, twice immersed and twice rolled, and the rolling rate is 80%. After the immersion, 6 times the mass of the modified polyester fiber is added for washing, and dried at 35°C for 18 hours to obtain an ultra-high moisture absorption and antistatic polyester fiber.

[0102] Example 5

[0103] This embodiment discloses a method for preparing ultra-high moisture absorption antistatic polyester fiber, comprising the following steps:

[0104] Step (1), preparation of modified benzisothiazolinone and modified cyclophosphazene

[0105] Wherein, the preparation of modified benzisothiazolinone comprises the following steps:

[0106] 1,2-Benzisothiazoline-3-one, dichloromethane and pyridine were mixed, methacryloyl chloride was added dropwise at room temperature for 30 minutes, and the reaction was carried out at room temperature for 1 hour after the addition was completed. After the reaction was completed, a reaction product was obtained, and water twice the mass of the reaction product was added to wash three times. The organic phase was taken, and anhydrous sodium sulfate of 20% of the mass of the organic phase was added, and the mixture was allowed to stand for dehydration for 12 hours, filtered, and the filtrate was taken and the solvent dichloromethane was removed by rotary evaporation at 35°C to obtain modified benzisothiazolinone;

[0107] Among them, the mass ratio of 1,2-benzisothiazolin-3-one, dichloromethane, pyridine and methacryloyl chloride is 5:33:4.1:5.5;

[0108] Wherein, the preparation of modified cyclophosphazene comprises the following steps:

[0109] Hexachlorocyclotriphosphazene is mixed with tetrahydrofuran, and an allylamine / triethylamine mixed solution is added dropwise at room temperature in a nitrogen atmosphere at a rotation speed of 1800 r / min for 20 minutes. After the addition is completed, the mixture is reacted in a nitrogen atmosphere at a temperature of 0°C for 8 hours. After the reaction is completed, the mixture is filtered and the filtrate is taken. Melamine is added to the filtrate, and the mixture is reacted for 16 hours in a nitrogen atmosphere at a temperature of 85°C. After the reaction is completed, the tetrahydrofuran and triethylamine are removed by rotary evaporation at a temperature of 50°C to obtain a reaction product, and water twice the mass of the reaction product is added for washing, and the mixture is dried at a temperature of 50°C for 12 hours to obtain a modified cyclophosphazene.

[0110] The mass ratio of hexachlorocyclotriphosphazene, tetrahydrofuran, allylamine / triethylamine mixed solution and melamine is 7:48:8:8; the allylamine / triethylamine mixed solution is prepared by mixing allylamine, triethylamine and tetrahydrofuran in a mass ratio of 1:8:0.7;

[0111] Step (2), mixing zinc aluminum oxide and ethanol with ultrasonic treatment, adding γ-methacryloxypropyltrimethoxysilane after ultrasonic treatment and mixing evenly, then adding 0.1 mol / L hydrochloric acid aqueous solution to adjust the pH value to 5, reacting for the first time at 70° C. for 10 h, filtering after the reaction, taking the filter cake, adding ethanol and water with a mass of 6 times that of the filter cake in sequence for washing, and drying at 50° C. for 12 h to obtain modified zinc aluminum oxide; wherein the mass ratio of zinc aluminum oxide, ethanol, and γ-methacryloxypropyltrimethoxysilane is 8:290:3;

[0112] Modified benzisothiazolinone, modified cyclophosphazene, modified zinc aluminum oxide, ammonium persulfate and water are mixed in a mass ratio of 30:60:100:6:1700, and reacted for a second time at 85°C in a nitrogen atmosphere for 5 hours. After the reaction is completed, the filter is filtered, and the filter cake is taken, and ethanol 8 times the mass of the filter cake is added for washing, and dried at 55°C for 10 hours to obtain a flame retardant antibacterial additive;

[0113] Step (3), mixing a flame retardant and antibacterial additive, calcium carbonate, and polyethylene terephthalate in a mass ratio of 3:5:92, melt-extruded through a twin-screw melt spinning machine under the condition that the temperature of each zone of the extruder is 270° C., spinning at a spinning speed of 2200 m / min, cooling, drawing, and chopping to obtain a modified polyester fiber crude product, mixing the modified polyester fiber crude product with a 1 mol / L hydrochloric acid aqueous solution in a mass ratio of 1:30, reacting at a temperature of 75° C. for 1 h, filtering after the reaction, taking a filter cake, adding water 5 times the mass of the filter cake for washing, and drying at a temperature of 95° C. for 3 h to obtain a modified polyester fiber with a fineness of 30D and an average length of 38 mm;

[0114] Wherein, during the melt spinning process, the cross section of the spinneret hole is in a cross shape, and the fiber cross section of the modified polyester fiber is in a cross shape;

[0115] Step (4), chitosan, acetic acid, 30wt% hydrogen peroxide aqueous solution, and water are mixed in a mass ratio of 45:25:40:1000, reacted at room temperature for 3 hours, and after the reaction is completed, sodium hydroxide is added to adjust the pH value to 9, filtered, and the filter cake is taken, washed with water 8 times the mass of the filter cake, and dried at 50°C for 18 hours to obtain modified chitosan;

[0116] Modified chitosan, acetic acid, malonic acid, sodium acetate and water are mixed in a mass ratio of 25:10:3:4:1000 to obtain a finishing liquid; the modified polyester fiber is mixed with the finishing liquid in a mass ratio of 1:20, immersed in room temperature for 1.5 hours, twice immersed and twice rolled, and the rolling rate is 80%. After the immersion, 5 times the mass of the modified polyester fiber is added for washing, and dried at 40°C for 12 hours to obtain an ultra-high moisture absorption and antistatic polyester fiber.

[0117] Comparative Example 1

[0118] This comparative example discloses a method for preparing an ultra-high moisture absorption antistatic polyester fiber, comprising the following steps:

[0119] Step (1), mixing zinc aluminum oxide and ethanol with ultrasound, adding γ-methacryloxypropyltrimethoxysilane after ultrasound and mixing evenly, then adding 0.1 mol / L hydrochloric acid aqueous solution to adjust the pH value to 5.5, reacting for the first time at 60° C. for 16 h, filtering after the reaction, taking the filter cake, adding ethanol and water with a mass of 8 times that of the filter cake in turn for washing, and drying at 50° C. for 12 h to obtain modified zinc aluminum oxide;

[0120] Among them, the mass ratio of zinc oxide aluminum, ethanol, and γ-methacryloxypropyltrimethoxysilane is 10:320:5;

[0121] Step (2), mixing modified zinc aluminum oxide, calcium carbonate, and polyethylene terephthalate in a mass ratio of 5:5:90, melt-extruded through a twin-screw melt spinning machine under the condition that the temperature of each zone of the extruder is 275° C., spinning at a spinning speed of 3200 m / min, cooling, drawing, and chopping to obtain a modified polyester fiber crude product, mixing the modified polyester fiber crude product with a 1 mol / L hydrochloric acid aqueous solution in a mass ratio of 1:30, reacting at a temperature of 75° C. for 1 h, filtering after the reaction, taking a filter cake, adding water 5 times the mass of the filter cake for washing, and drying at a temperature of 95° C. for 3 h to obtain a modified polyester fiber with a fineness of 15D and an average length of 38 mm;

[0122] Wherein, during the melt spinning process, the cross section of the spinneret hole is in a cross shape, and the fiber cross section of the modified polyester fiber is in a cross shape;

[0123] Step (3), chitosan, acetic acid, 30wt% hydrogen peroxide aqueous solution, and water are mixed in a mass ratio of 50:25:40:1000, and reacted at room temperature for 3 hours. After the reaction is completed, sodium hydroxide is added to adjust the pH value to 8, and the filter cake is filtered, and washed with water 5 times the mass of the filter cake, and dried at 60°C for 10 hours to obtain modified chitosan;

[0124] Modified chitosan, acetic acid, malonic acid, sodium acetate and water are mixed in a mass ratio of 30:20:3:4:1000 to obtain a finishing liquid; the modified polyester fiber is mixed with the finishing liquid in a mass ratio of 1:20, immersed in the mixture for 1.5 hours at room temperature, and rolled twice with a rolling rate of 80%. After the immersion, water 5 times the mass of the modified polyester fiber is added for washing, and the fiber is dried at 40°C for 12 hours to obtain an ultra-high moisture absorption and antistatic polyester fiber.

[0125] Comparative Example 2

[0126] This comparative example discloses a method for preparing an ultra-high moisture absorption antistatic polyester fiber, comprising the following steps:

[0127] Step (1), preparation of modified benzisothiazolinone and modified cyclophosphazene

[0128] Wherein, the preparation of modified benzisothiazolinone comprises the following steps:

[0129] 1,2-Benzisothiazoline-3-one, dichloromethane and pyridine were mixed, methacryloyl chloride was added dropwise at room temperature for 30 minutes, and the reaction was carried out at room temperature for 1 hour after the addition was completed. After the reaction was completed, a reaction product was obtained, and water 5 times the mass of the reaction product was added to wash three times. The organic phase was taken, and anhydrous sodium sulfate 20% of the mass of the organic phase was added. The organic phase was allowed to stand for dehydration for 12 hours, filtered, and the filtrate was taken. The solvent dichloromethane was removed by rotary evaporation at 35°C to obtain modified benzisothiazolinone;

[0130] Among them, the mass ratio of 1,2-benzisothiazolin-3-one, dichloromethane, pyridine and methacryloyl chloride is 5.5:36:4.4:6;

[0131] Wherein, the preparation of modified cyclophosphazene comprises the following steps:

[0132] Mix hexachlorocyclotriphosphazene with tetrahydrofuran, add a mixed solution of allylamine / triethylamine dropwise at room temperature in a nitrogen atmosphere at a rotation speed of 2000 r / min for 30 min, react for 4 h in a nitrogen atmosphere at 5°C after the addition is complete, filter and take the filtrate after the reaction is complete, add melamine to the filtrate, continue to react for 16 h in a nitrogen atmosphere at 85°C, and after the reaction is complete, remove tetrahydrofuran and triethylamine by rotary evaporation at 60°C to obtain a reaction product, add water twice the mass of the reaction product for washing, and dry at 50°C for 12 h to obtain a modified cyclophosphazene;

[0133] The mass ratio of hexachlorocyclotriphosphazene, tetrahydrofuran, allylamine / triethylamine mixed solution and melamine is 7:50:8:8; the allylamine / triethylamine mixed solution is prepared by mixing allylamine, triethylamine and tetrahydrofuran in a mass ratio of 1:7:0.5;

[0134] Step (2), mixing the modified benzisothiazolinone, the modified cyclophosphazene, ammonium persulfate and water in a mass ratio of 60:130:6:1800, reacting for a second time in a nitrogen atmosphere at 85°C for 5 hours, filtering after the reaction, taking the filter cake, adding ethanol 8 times the mass of the filter cake for washing, and drying at 50°C for 12 hours to obtain a flame retardant antibacterial additive;

[0135] Step (3), mixing a flame retardant and antibacterial additive, calcium carbonate, and polyethylene terephthalate in a mass ratio of 3:5:92, melt-extruded through a twin-screw melt spinning machine under the condition that the temperature of each zone of the extruder is 275° C., spinning at a spinning speed of 3200 m / min, cooling, drawing, and chopping to obtain a modified polyester fiber crude product, mixing the modified polyester fiber crude product with a 1 mol / L hydrochloric acid aqueous solution in a mass ratio of 1:30, reacting at a temperature of 75° C. for 1 h, filtering after the reaction, taking a filter cake, adding water 5 times the mass of the filter cake for washing, and drying at a temperature of 95° C. for 3 h to obtain an ultra-high moisture absorption antistatic polyester fiber with a fineness of 15D and an average length of 38 mm;

[0136] In the process of melt spinning, the cross section of the spinneret hole is in the shape of a cross, and the fiber cross section of the ultra-high moisture absorption antistatic polyester fiber is in the shape of a cross.

[0137] Comparative Example 3

[0138] This comparative example discloses a method for preparing an ultra-high moisture absorption antistatic polyester fiber, comprising the following steps:

[0139] Step (1), preparation of modified benzisothiazolinone and modified cyclophosphazene

[0140] Wherein, the preparation of modified benzisothiazolinone comprises the following steps:

[0141] 1,2-Benzisothiazoline-3-one, dichloromethane and pyridine were mixed, methacryloyl chloride was added dropwise at room temperature for 30 minutes, and the reaction was carried out at room temperature for 1 hour after the addition was completed. After the reaction was completed, a reaction product was obtained, and water 5 times the mass of the reaction product was added to wash three times. The organic phase was taken, and anhydrous sodium sulfate 20% of the mass of the organic phase was added. The organic phase was allowed to stand for dehydration for 12 hours, filtered, and the filtrate was taken. The solvent dichloromethane was removed by rotary evaporation at 35°C to obtain modified benzisothiazolinone;

[0142] Among them, the mass ratio of 1,2-benzisothiazolin-3-one, dichloromethane, pyridine and methacryloyl chloride is 5.5:36:4.4:6;

[0143] Wherein, the preparation of modified cyclophosphazene comprises the following steps:

[0144] Mix hexachlorocyclotriphosphazene with tetrahydrofuran, add a mixed solution of allylamine / triethylamine dropwise at room temperature in a nitrogen atmosphere at a rotation speed of 2000 r / min for 30 min, react for 4 h in a nitrogen atmosphere at 5°C after the addition is complete, filter and take the filtrate after the reaction is complete, add melamine to the filtrate, continue to react for 16 h in a nitrogen atmosphere at 85°C, and after the reaction is complete, remove tetrahydrofuran and triethylamine by rotary evaporation at 60°C to obtain a reaction product, add water twice the mass of the reaction product for washing, and dry at 50°C for 12 h to obtain a modified cyclophosphazene;

[0145] The mass ratio of hexachlorocyclotriphosphazene, tetrahydrofuran, allylamine / triethylamine mixed solution and melamine is 7:50:8:8; the allylamine / triethylamine mixed solution is prepared by mixing allylamine, triethylamine and tetrahydrofuran in a mass ratio of 1:7:0.5;

[0146] Step (2), mixing zinc aluminum oxide and ethanol with ultrasonic treatment, adding γ-methacryloxypropyltrimethoxysilane after ultrasonic treatment and mixing evenly, then adding 0.1 mol / L hydrochloric acid aqueous solution to adjust the pH value to 5.5, reacting for the first time at 60° C. for 16 h, filtering after the reaction, taking the filter cake, adding ethanol and water in an amount of 8 times the mass of the filter cake to wash in sequence, and drying at 50° C. for 12 h to obtain modified zinc aluminum oxide; wherein the mass ratio of zinc aluminum oxide, ethanol, and γ-methacryloxypropyltrimethoxysilane is 10:320:5;

[0147] Modified benzisothiazolinone, modified cyclophosphazene, modified zinc aluminum oxide, ammonium persulfate and water were mixed in a mass ratio of 30:60:100:6:1800, and reacted for a second time at 85°C in a nitrogen atmosphere for 5 hours. After the reaction, the mixture was filtered, the filter cake was taken, ethanol in an amount of 8 times the mass of the filter cake was added for washing, and the mixture was dried at 50°C for 12 hours to obtain a flame retardant antibacterial additive.

[0148] Step (3), mixing a flame retardant and antibacterial additive and polyethylene terephthalate in a mass ratio of 5:95, melt-extrude through a twin-screw melt spinning machine under the condition that the temperature of each zone of the extruder is 275° C., spinning at a spinning speed of 3200 m / min, cooling, drawing, and chopping to obtain a modified polyester fiber crude product, mixing the modified polyester fiber crude product with a 1 mol / L hydrochloric acid aqueous solution in a mass ratio of 1:30, reacting at a temperature of 75° C. for 1 h, filtering after the reaction, taking a filter cake, adding water 5 times the mass of the filter cake for washing, and drying at a temperature of 95° C. for 3 h to obtain an ultra-high moisture absorption antistatic polyester fiber with a fineness of 15D and an average length of 38 mm;

[0149] In the process of melt spinning, the cross section of the spinneret hole is in the shape of a cross, and the fiber cross section of the ultra-high moisture absorption antistatic polyester fiber is in the shape of a cross.

[0150] In the above embodiments and comparative examples: 1,2-benzisothiazolin-3-one is from Shandong Jinshengtai Chemical Co., Ltd., CAS No.: 2634-33-5; dichloromethane is from Dongguan Xunye Chemical Reagent Co., Ltd., CAS No.: 75-09-2; pyridine is from Wuxi Jingke Chemical Co., Ltd., CAS No.: 110-86-1; methacryloyl chloride is from Wuhan Kemik Biopharmaceutical Technology Co., Ltd., CAS No.: 920-46-7; anhydrous sodium sulfate is from Tianjin Jinhui Taiya Chemical Reagent Co., Ltd., CAS No.: 7757-82-6; hexachlorocyclotriphosphazene is from Hubei Chengfeng Chemical Co., Ltd. Company, CAS number: 940-71-6; tetrahydrofuran comes from Guangzhou Jiatu Technology Co., Ltd., CAS number: 109-99-9; allylamine comes from Hubei Xinghengye Technology Co., Ltd., CAS number: 107-11-9; triethylamine comes from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS number: 121-44-8; melamine comes from Guangdong Fangxin Biotechnology Co., Ltd., CAS number: 108-78-1; zinc aluminum oxide comes from Guangzhou Hongwu Material Technology Co., Ltd., particle size 30nm, ZnO:Al2O3=99:1, CAS number: 12068-53-0; ethanol From Shanghai Yishi Chemical Co., Ltd., CAS No.: 64-17-5; γ-methacryloxypropyltrimethoxysilane from Shandong Shangwei Chemical Import and Export Co., Ltd., CAS No.: 2530-85-0; hydrochloric acid aqueous solution from Shanghai Yuanye Biotechnology Co., Ltd., item No. B62243, model hydrogen chloride standard solution; ammonium persulfate from Nanjing Chemical Reagent Co., Ltd., CAS No.: 7727-54-0; calcium carbonate from Ningbo Luofei Nanotechnology Co., Ltd., particle size 1-2μm, CAS No.: 471-34-1; chitosan from Shanghai McLean Biochemical Technology Co., Ltd., item No. C 850346, Mw=300000, CAS No.: 9012-76-4; acetic acid was from Wuxi Jingke Chemical Co., Ltd., model analytical grade, CAS No.: 64-19-7; aqueous hydrogen peroxide solution was from Tianjin Damao Chemical Reagent Factory, model analytical grade, CAS No.: 7722-84-1; sodium hydroxide was from Wuxi Jingke Chemical Co., Ltd., CAS No.: 1310-73-2; malonic acid was from Shenzhen Hengwang Chemical Technology Co., Ltd., model analytical grade, CAS No.: 141-82-2; sodium acetate was from Jining Fangyu Chemical Co., Ltd., CAS No.: 127-09-3.

[0151] Test example

[0152] (1) Antibacterial performance, hygroscopicity and antistatic performance tests

[0153] The antibacterial performance, hygroscopicity and antistatic performance of the ultra-high hygroscopic antistatic polyester fibers prepared in Examples 1-5 and Comparative Examples 1-3 were tested. The specific test results are shown in Table 1:

[0154] Table 1

[0155]

[0156]

[0157] The tests of various indicators in Table 1 are based on the following standards: the antibacterial rate is determined by GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", in which Escherichia coli is selected as the bacteria; the moisture absorption rate is calculated by (the mass of water contained in the fiber after full moisture absorption / fiber dry weight) × 100%; the antistatic grade and static voltage half-life are determined by GB / T12703.1-2008 "Evaluation of static voltage performance of textiles Part 1: Static voltage half-life".

[0158] It can be seen from the test results in Table 1 that the ultra-high hygroscopic antistatic polyester fiber prepared in the present invention has high hygroscopicity and excellent antibacterial and antistatic properties.

[0159] In the present invention, 1,2-benzisothiazolin-3-one with antibacterial property is reacted with methacryloyl chloride to undergo nucleophilic substitution reaction, so that the obtained modified benzisothiazolinone has a double bond, and the modified benzisothiazolinone is mixed with modified zinc oxide aluminum and modified cyclophosphazene having carbon-carbon double bonds for copolymerization, so that the dispersibility of zinc oxide aluminum in a matrix and the stability of the modified benzisothiazolinone and the modified cyclophosphazene are improved, so that the modified benzisothiazolinone and the modified cyclophosphazene are not easy to migrate, and the obtained flame retardant and antibacterial additive has flame retardant, antibacterial and antistatic effects.

[0160] The present invention obtains modified polyester fiber by adding a porogen and a flame retardant and antibacterial additive to polyethylene terephthalate, and performing melt spinning and acid treatment. The amino groups on the surface of the flame retardant and antibacterial additive react with the terminal carboxyl groups of the polyethylene terephthalate molecular chain in a molten state to graft the flame retardant and antibacterial additive onto the chain segments of polyethylene terephthalate, thereby making it have better dispersibility and compatibility in polyethylene terephthalate, and improving the antibacterial and flame retardant properties and mechanical properties of polyester; the porogen is dissolved during the acid treatment process, so that the obtained modified polyester fiber has a microporous structure, thereby improving the hygroscopicity of the modified polyester fiber, and at the same time, since the modified polyester fiber has polar amide bonds, it can form hydrogen bonds with water molecules, so the hydrophilicity of the fiber is increased to a certain extent, thereby further improving the hygroscopicity of the modified polyester fiber.

[0161] The present invention impregnates the modified polyester fiber with low molecular weight modified chitosan. Since the modified chitosan molecule contains a large amount of amino and hydroxyl groups and has antibacterial effect, the microporous structure on the modified polyester fiber increases the surface area of ​​the fiber and can load more modified chitosan, thereby further improving the hygroscopicity of the modified polyester fiber.

[0162] In Comparative Example 1, modified benzisothiazolinone and modified cyclophosphazene were not added, and only zinc aluminum oxide was added. The antibacterial effect of modified benzisothiazolinone on the fiber as an antibacterial agent was lacking, and the antibacterial property of the obtained fiber was reduced. Although the fiber was loaded with modified chitosan after the impregnation treatment, the antibacterial property of the final comparative example 1 was still lower than that of the embodiment. In addition, since no modified cyclophosphazene was added, there was no amidation reaction between the amino group and the terminal carboxyl group of the polyethylene terephthalate molecular chain in the molten state, and no polar amide bond could be generated, so the hygroscopicity of the obtained fiber was lower than that of the embodiment.

[0163] In Comparative Example 2, modified zinc aluminum oxide was not added, and the obtained fiber was not impregnated with modified chitosan. Since the fiber surface was not loaded with modified chitosan, and the flame retardant antibacterial additive was fixed in the fiber through amide bonds and was not easily dissolved, the antibacterial property of the fiber was less reduced during the washing process, but the overall antibacterial property was lower than that of the embodiment. In addition, since modified zinc aluminum oxide was not added to the fiber, the conductivity of the fiber decreased, and the fiber was not loaded with modified chitosan, the hygroscopicity of the fiber decreased, so the hygroscopicity and antistatic property of the obtained Comparative Example 2 were lower than those of the embodiment.

[0164] In Comparative Example 3, no porogen was added, and the obtained fiber was not impregnated with modified chitosan. Since the fiber surface was not loaded with modified chitosan, and the flame retardant antibacterial additive was fixed in the fiber through amide bonds and was not easily dissolved, the antibacterial property of the fiber was less reduced during the washing process, but the overall antibacterial property was lower than that of the embodiment. In addition, since no porogen was added to the fiber, the fiber did not have a microporous structure, and the fiber was not loaded with modified chitosan, the hygroscopicity of the fiber decreased, so the hygroscopicity and antistatic property of the obtained Comparative Example 2 were lower than those of the embodiment.

[0165] (2) Flame retardant performance test

[0166] The ultra-high moisture absorption and antistatic polyester fibers prepared in Examples 1-5 and Comparative Examples 1-3 were spun into yarns as warp and weft respectively, and the yarn counts were all 40S (English counts), and woven to obtain fabrics 1-8; wherein the weight of fabrics 1-8 was 200 g / m 2 .

[0167] The flame retardant performance of fabrics 1-8 was tested. The specific test results are shown in Table 2:

[0168] Table 2

[0169]

[0170] The detection of each index in Table 2 is based on the following standards: The limiting oxygen index is determined by GB / T5454-1997 "Textile Combustion Performance Test-Oxygen Index Method".

[0171] It can be seen from the test results in Table 2 that the ultra-high moisture absorption antistatic polyester fiber prepared in the present invention has excellent flame retardant properties.

[0172] In the present invention, hexachlorocyclotriphosphazene and allylamine undergo a nucleophilic substitution reaction, so that allylamine is grafted onto the hexachlorocyclotriphosphazene, and after the reaction, the remaining chlorine on the hexachlorocyclotriphosphazene undergoes a nucleophilic substitution reaction with melamine again to obtain a modified cyclophosphazene having a triazine structure and a double bond. The triazine structure and the phosphazene structure in the modified cyclophosphazene together constitute an intumescent flame retardant, which has a synergistic flame retardant effect, and the double bond group provides an active group for the modified cyclophosphazene, so that it can be used as a reaction monomer, and is combined with other monomers containing double bonds and a carrier through a polymerization reaction between double bonds, so that it is not easy to migrate.

[0173] In Comparative Example 1, no modified benzisothiazolinone and modified cyclophosphazene were added, and only zinc oxide aluminum was added. The flame retardant effect of modified cyclophosphazene on the fiber was lacking, and the flame retardancy of the obtained fiber was reduced. The flame retardancy of the final fabric 6 was lower than that of the embodiment.

[0174] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing ultra-high moisture absorption antistatic polyester fiber, characterized in that: The following steps are involved: Step (1), preparation of modified benzisothiazolinone and modified cyclophosphazene Wherein, the preparation of modified benzisothiazolinone comprises the following steps: Mix 1,2-benzisothiazolin-3-one, dichloromethane and pyridine, add methacryloyl chloride dropwise, react after the addition is complete, wash, dehydrate, filter, take the filtrate, and remove the solvent dichloromethane by rotary evaporation to obtain modified benzisothiazolinone; Wherein, the preparation of modified cyclophosphazene comprises the following steps: The hexachlorocyclotriphosphazene is mixed with tetrahydrofuran, and a mixed solution of allylamine / triethylamine is added dropwise. After the addition is completed, the mixture is reacted. After the reaction is completed, the mixture is filtered and the filtrate is taken. After the reaction is completed, melamine is added to the filtrate and the reaction is continued. After the reaction is completed, the tetrahydrofuran and triethylamine are removed by rotary evaporation, and the mixture is washed and dried to obtain a modified cyclophosphazene. Step (2), mixing zinc aluminum oxide and ethanol by ultrasonication, adding γ-methacryloxypropyltrimethoxysilane after ultrasonication and mixing evenly, then adding a regulator to adjust the pH value, and performing a first reaction. After the reaction is completed, filtering, washing, and drying to obtain modified zinc aluminum oxide; The modified benzisothiazolinone, the modified cyclophosphazene, the modified zinc oxide aluminum, ammonium persulfate and water are mixed, reacted for the second time, filtered, washed and dried after the reaction is completed, and a flame retardant antibacterial additive is obtained; Step (3), mixing the flame retardant and antibacterial additive, calcium carbonate and polyethylene terephthalate, melt spinning, cooling, drawing and chopping to obtain a crude modified polyester fiber product, mixing the crude modified polyester fiber product with an aqueous solution of hydrochloric acid, reacting, filtering, washing and drying after the reaction is completed to obtain the modified polyester fiber; Step (4), mixing chitosan, acetic acid, aqueous hydrogen peroxide solution and water, reacting, adding a regulator to adjust the pH value after the reaction is completed, filtering, washing and drying to obtain modified chitosan; The modified chitosan, acetic acid, malonic acid, sodium acetate and water are mixed to obtain a finishing liquid; the modified polyester fiber is mixed with the finishing liquid, immersed, and after the immersion is completed, washed and dried to obtain an ultra-high moisture absorption antistatic polyester fiber.

2. The method for preparing a super-high moisture absorption antistatic polyester fiber according to claim 1, characterized in that: In the step (1), when preparing the modified benzisothiazolinone: the mass ratio of 1,2-benzisothiazolin-3-one, dichloromethane, pyridine and methacryloyl chloride is 5-5.5:33-36:4-4.4:5.5-6; the dropping condition is: dropping at room temperature for 20-30 minutes; the reaction condition is: reacting at room temperature for 1-2 hours.

3. The method for preparing a super-high moisture absorption antistatic polyester fiber according to claim 1, characterized in that: In the step (1), when preparing the modified cyclophosphazene, the mass ratio of hexachlorocyclotriphosphazene, tetrahydrofuran, allylamine / triethylamine mixed solution, and melamine is 6.5-7:45-50:6.5-8:6-8; the dropping conditions are: dropping for 20-30 minutes at a speed of 1500-2000 r / min and room temperature in a nitrogen atmosphere; the reaction conditions are: reacting for 4-8 hours at a temperature of 0-5° C. in a nitrogen atmosphere; and the continued reaction conditions are: continuing the reaction for 16-18 hours at a temperature of 80-85° C. in a nitrogen atmosphere.

4. The method for preparing a super-high moisture absorption antistatic polyester fiber according to claim 1, characterized in that: In the step (2), the mass ratio of zinc oxide aluminum, ethanol and γ-methacryloxypropyltrimethoxysilane is 8-10:280-320:3-5; the adjusted pH value is 5-5.5; the first reaction conditions are: the first reaction is carried out at a temperature of 60-70° C. for 10-16 hours.

5. The method for preparing a super-high moisture absorption antistatic polyester fiber according to claim 1, characterized in that: In the step (2), the mass ratio of modified benzisothiazolinone, modified cyclophosphazene, modified zinc oxide aluminum, ammonium persulfate and water is 25-30:55-60:100:5-6:1500-1800; the second reaction conditions are: in a nitrogen atmosphere, at a temperature of 80-85° C., and the second reaction is carried out for 5-6 hours.

6. The method for preparing a super-high moisture absorption antistatic polyester fiber according to claim 1, characterized in that: In the step (3), the mass ratio of the flame retardant and antibacterial additive, calcium carbonate and polyethylene terephthalate is 3-5:5:90-92; the melt spinning conditions are: melt extrusion through a twin-screw melt spinning machine under the condition that the temperature of each zone of the extruder is 270-275° C., and spinning is carried out at a spinning speed of 1800-3200 m / min.

7. The method for preparing a super-high moisture absorption antistatic polyester fiber according to claim 1, characterized in that: In the step (3), the mass ratio of the modified polyester fiber crude product to the hydrochloric acid aqueous solution is 1:30; the reaction conditions are: reaction at a temperature of 75-80° C. for 0.5-1 h; the fineness of the modified polyester fiber is 15-30D, the average length is 38 mm, and the fiber cross section is a cross shape.

8. The method for preparing a super-high moisture absorption antistatic polyester fiber according to claim 1, characterized in that: In the step (4), the mass ratio of chitosan, acetic acid, aqueous hydrogen peroxide solution and water is 30-50:20-25:30-40:1000, and the aqueous hydrogen peroxide solution is 30 wt % aqueous hydrogen peroxide solution; and the reaction conditions are: reacting at room temperature for 2-3 hours.

9. The method for preparing a super-high moisture absorption antistatic polyester fiber according to claim 1, characterized in that: In the step (4), the mass ratio of modified chitosan, acetic acid, malonic acid, sodium acetate and water is 25-30:10-20:3:4:1000; the mass ratio of modified polyester fiber to finishing liquid is 1:20; the dipping operation includes: dipping at room temperature for 1-1.5 hours, two dippings and two rollings, and the rolling rate is 80%.

10. An ultra-high hygroscopic antistatic polyester fiber prepared by the method for preparing an ultra-high hygroscopic antistatic polyester fiber as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of antistatic and antibacterial fabric

    CN110616472A

Cited By

  • Antistatic polyester fiber and preparation method thereof

    CN120719420A

  • Preparation process of anti-static polylactic acid superfine fiber fabric

    CN120759000A

  • Preparation process of graphene reinforced porous hollow polyester fiber

    CN121228393A

  • Preparation process of graphene reinforced porous hollow polyester fiber

    CN121228393B